PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PELECEHAN SEKSUAL TERHADAP ANAK DI PENGADILAN NEGERI KELAS I A PEKANBARU - Andre David Hasintongan Sitanggang; Evi Deliana; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The criminal act regulations that are put in place are to protect the public and which make such actions punishable under a criminal article. It is very important to know, the forms of sexual violence against children have a very broad scope, including, rape, sodomy, oral sex, sexual gestures (visual sexual assaults including exhibitionism), sexual rheumatism (verbal sexual assaults, sexual harassment, child prostitution and clitoral circumcision in girls). In its protection, children are also subject to a separate judiciary namely Law Number 11 of 2012 concerning the Criminal Justice System for Children to aim to provide the best interests of children.Scientific writing aims to: First, to find out the application of criminal sanctions against perpetrators of criminal acts of sexual abuse of children in the Pekanbaru District Court. Second, to find out the basic considerations of judges in imposing sanctions for sexual harassment in the Pekanbaru District Court.This thesis writing uses sociological juridical research methods. Sociological juridical legal research that uses secondary data as initial data, which is then followed by primary data or field data, examines the effectiveness of a law and research that wants to find a relationship (correlation) between various symptoms or variables as data collection tools consisting of studies documents and interviews.From the results of the research problem according to Law No. 11 of 2012 concerning the Child Criminal Justice System and Law No. 35 of 2014 concerning Child Protection. By using the theory of justice the Judge has followed aspects in the application of sanctions mandated by the regulations in force today, and the Judge also pays attention to facts at trial, witness statements, evidence and visum et repertum. The judge also looked at aspects of the environment and the people around the perpetrators. And also consider the future of the victims and perpetrators alike.Keywords: Application of Sanctions, Criminal Purpose, Child Sexual abuse